Exercise 1.1 (Math 10)

Question 1. Write the following quadratic equations in the standard form and point out pure quadratic equations. $\pmb{ (i). \;\;\;\;\; (x + 7) (x − 3) = -7}$ Solution: The given quadratic equation is $$(x + 7) (x − 3) = -7 \;\;\;\;\; (i)$$ Multiplying the expressions \$ (x + 7)…

Solution of Quadratic Equation by factorization

In this method, write the quadratic equation in the standard form as ax2 + bx + c = 0          (i) If two numbers r and s can be found for the equation (i) such that r + s = b and rs = ac then ax2 + bx + c can be factorized into two…

Solution of Quadratic Equation by Completing Square

To solve a quadratic equation by the method of completing square is illustrated through the following examples. Example Solve the equation x2 − 3x − 4 = 0 by completing square. Solution: x2 − 3x − 4 = 0          (i) Shifting constant term −4 to the right, we have x2 − 3x = 4         …

Solution of Quadratic Equations

To find the solution set of a quadratic equation, following methods are used: factorization completing square use of quadratic formula